Concept «Woman» in the poetic works of Mariyam Khakimzhanova - Abubakirova, Г.Н.; Kaiypbayeva, А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
A woman, rocking the world with one hand and the cradle with another hand, has always held a special place in Kazakh society. The fate of women as counsellors to husbands, mentors to children is sometimes complicated and variable. Every woman is a well-bred daughter-in-law, beloved mother, respected sister, dear grandmother. Therefore, the theme of a woman is one of the eternal themes. Especially women’s fate, sadness, feelings became the basis for many works. Poets and writers, portraying a woman, along with the peculiarities of national customs, did not forget about the secrets of the spiritual world, the peculiarities of national knowledge and education. And in the works of Mariyam Khakimzhanova, who became the object of our research, it can be noted that the linguistic units that define the concept of “woman” are given in accordance with the national worldview. In the article, the lexeme «woman» is considered on the basis of different poems